THE QUANTITATIVE AND QUALITATIVE ANALYSIS OF PUBLIC ADMINISTRATION REFORMS IN POST-COMMUNIST COUNTRIES - Nakrošis, Vitalis (Baltic Journal of Political Science, 2018)
In this article we describe the adoption and execution of public administration reforms in Central and Eastern Europe between 2008 and 2013, as well as examine whether post-communist countries differ from other groups of European countries in terms of the substance of reforms and their implementation process. Instead of following popular Western administrative theoretical frames, we adopt the policy process approach. We focus on the role of policy actors during reform policymaking and implementation at the level of policy subsystems. More specifically, we employ the rational-comprehensive and garbage can perspectives to understand the reform processes in the post-communist region. Our research is based on the statistical analysis of survey data and two case studies of reforms initiated by the 2008-2012 Lithuanian government. The article concludes that countries in Central and Eastern Europe share some common characteristics: they focused on the issues of civil service and public or administrative services, their reform policy was often formulated on a top-down basis, and its execution often lacked adequate capacities. Despite a rational reform façade in these countries, the implementation of governance change appears to be quite erratic, as anticipated in the garbage can perspective. This can have negative consequences on the effectiveness of public policy, continuing to generate public distrust in post-communist state institutions.